NI-11 USEFULNESS OF MRI ARTERIAL SPIN LABELING METHOD FOR DIAGNOSING BRAIN TUMOR. (3rd December 2022) - Hiu, Takeshi; Shiozaki, Eri; Ishikawa, Ayano; Morikawa, Minoru; Matsuo, Ayaka; Yoshida, Michiharu; Baba, Shiro; Ujifuku, Kenta; Yoshida, Koichi; Morofuji, Yoichi; Izumo, Tsuyoshi; Matsuo, Takayuki
Abstract: Background: Diagnosis of hemangioblastoma by magnetic resonance imaging (MRI) can sometimes be difficult when the tumor is a solid mass in the posterior fossa. We therefore evaluated perfusion images and diffusion-weighted images as brain function images to diagnose hemangioblastoma in order to obtain the most useful quantitative features. Methods: Forty-five posterior fossa tumors whose pathological diagnosis was confirmed by surgery were included in groups A (18 hemangioblastomas) and B (non-hemangioblastoma 27 cases: metastatic brain tumor 8 cases, pilocytic astrocytoma 6 cases, and other 13 cases). All cases were imaged by 3.0-Tesla MRI, with arterial spin labeling (ASL) as the relative value from the CBF map to the region of interest (ROI) in the contralateral hemisphere as perfusion image. Among 45 cases, 27 cases were evaluated with both ASL and dynamic susceptibility contrast (DSC) as rCBF, rCBV, corrected CBV, and K2. The ROI was set to match the contrast-enhanced part, and the two groups were compared and examined. Results: The relative ASL value of group A and the corrected CBV in DSC were significantly higher than group B (p < 0.001). In contrast, the ADC showed no marked difference between the two groups. In the distinction between the two groups, the receiver operating characteristic (ROC) analysis showed that the area under the curve (AUC) of the relative ASL value was significantly higher than the other parameters (AUC 0.995, cut-off value 2.34, sensitivity 100%, specificity 99.5%). Conclusions: The non-contrast ASL method was extremely useful for diagnosing hemangioblastoma in posterior fossa tumors. Non contrast ASL can be used instead of contrast-enhanced DSC in diagnosing posterior fossa hemangioblastoma.